Differential utilization patterns of dissolved organic phosphorus compounds by heterotrophic bacteria in two mountain lakes. Issue 9 (15th June 2016) - Rofner, Carina; Sommaruga, Ruben; Pérez, María Teresa
Abstract : Although phosphorus limitation is common in freshwaters and bacteria are known to use dissolved organic phosphorus (DOP), little is known about how efficiently DOP compounds are taken up by individual bacterial taxa. Here, we assessed bacterial uptake of three model DOP substrates in two mountain lakes and examined whether DOP uptake followed concentration-dependent patterns. We determined bulk uptake rates by the bacterioplankton and examined bacterial taxon-specific substrate uptake patterns using microautoradiography combined with catalyzed reporter deposition–fluorescence in situ hybridization. Our results show that in the oligotrophic alpine lake, bacteria took up ATP, glucose-6-phosphate and glycerol-3-phosphate to similar extents (mean 29.7 ± 4.3% Bacteria ), whereas in the subalpine mesotrophic lake, ca. 40% of bacteria took up glucose-6-phosphate, but only ∼20% took up ATP or glycerol-3-phosphate. In both lakes, the R-BT cluster of Betaproteobacteria (lineage of genus Limnohabitans ) was over-represented in glucose-6-phosphate and glycerol-3-phosphate uptake, whereas AcI Actinobacteria were under-represented in the uptake of those substrates. Alphaproteobacteria and Bacteroidetes contributed to DOP uptake proportionally to their in situ abundance. Our results demonstrate that R-BT Betaproteobacteria are the most active bacteria in DOP acquisition, whereas the abundant AcI Actinobacteria may either lack high affinity DOP uptake systems or have reduced phosphorus requirements. Abstract : In phosphorus-limited mountain lakes, the most abundant taxa, the AcI lineage of Actinobacteria and the R-BT cluster of Betaproteobacteria, exhibit strikingly different dissolved organic phosphorus uptake patterns. Abstract :